Contemporary Issues and Development in the Global Halal Industry [electronic resource] : Selected Papers from the International Halal Conference 2014 - Ab. Manan, Siti Khadijah; Abd Rahman, Fadilah; Sahri, Mardhiyyah; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book features more than 50 papers presented at the International Halal Conference 2014, which was held in Istanbul and organised by the Academy of Contemporary Islamic Studies of Universiti Teknologi MARA. It addresses the challenges facing Muslims involved in halal industries in meeting the increasing global demand. The papers cover topics such as halal food, halal pharmaceuticals, halal cosmetics and personal care, halal logistics, halal testing and analysis and ethics in the halal industry. Overall, the volume offers a comprehensive point of view on Islamic principles relating to the halal business, industry, culture, food, safety, finance and other aspects of life. The contributors include experts from various disciplines who apply a variety of scientific research methodologies. They present perspectives that range from the experimental to the philosophical. This volume will appeal to scholars at all levels of qualification and experience who seek a clearer understanding of important issues in the halal industry.
Part 1: Halal Standard &Policy -- Part 2: Halal Research & Education -- Part 3: Halal Business & Industry -- Part 4: Halal Food & Safety -- Part 5: Halal Services.
Keywords: Social sciences; Religion; Market research